PENGARUH LITERASI KEUANGAN DIGITAL, PERSEPSI RESIKO, KEPERCAYAAN FINTECH, DAN FINANCIAL SELF-EFFICACY TERHADAP PERILAKU INVESTASI GENERASI Z PADA PLATFORM BIBIT DENGAN ROBO ADVISOR SEBAGAI VARIABEL MODERASI - Nabiatul Qomariyah; Aldila Septiana (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the influence of digital financial literacy, risk perception, fintech trust, and financial self-efficacy on Generation Z's investment behavior on the Bibit digital investment platform with robo-advisors as a moderating variable. This study used a quantitative approach with accidental sampling technique involving 133 respondents from Generation Z. Data collection was conducted through a questionnaire using a Likert scale, then analyzed using multiple linear regression with a Moderated Regression Analysis (MRA) approach. The results showed that digital financial literacy has a positive and significant effect on investment behavior. Conversely, risk perception and financial self-efficacy have a negative and significant effect, while fintech trust has no significant effect on investment behavior. In addition, robo-advisors are able to weaken the influence of digital financial literacy on investment behavior, but strengthen the influence of risk perception, fintech trust, and financial self-efficacy. Simultaneously, all independent variables have a significant effect on Generation Z's investment behavior. The novelty of this study lies in the use of robo-advisors as a moderating variable in analyzing Generation Z's investment behavior on digital investment platforms amidst the increasing adoption of fintech and digital financial transformation in Indonesia.